UNTOUCHABLE COST DALAM PEMBENTUKAN HARGA POKOK PEROLEHAN PARA BANDOL TEMBAKAU DI MADURA - Nawafil, Toriqin; Baihaki, Ach.; Zakhra, Aminatus (Journal MISSY (Management and Business Strategy), 2023)
This study aims to analyze the process of the emergence of untouchable costs in the formation of the cost of acquisition of tobacco bandol in Madura. By using a descriptive qualitative approach. The results of this study indicate that, Untouchable costs arise because bandol ignores the expenditure of costs incurred during the tobacco trading process, starting from the announcement, purchasing, delivery, sorting, and weighing processes. So that that expenditure in the form of money, goods, services, or other resources that are issued outside the purchase price are only considered as operational costs. The error cost of sales will be trouble on the operasional profit of the entity.